A passagem da escola tradicional para a escola na sociedade do fluxo - Gonçalves, Luciana Lívia (2020)
The so-called Traditional Schools emerged under the Enlightenment ideal of the bourgeoisie's progress, in the 19th century, and to meet the need for labor work for the industrial society (SAVIANI, 1999; SIBILIA, 2012; VEIGA-NETO, 2003). However, the mobile digital technologies, which allow us to participate anywhere and at any time in the digital flow, have significantly transformed the way we inhabit the contemporary world. It has modified the way we build and maintain our social relationships, work, consumption, communication, the way we store our data and memories, entertain ourselves, access information, and acquire knowledge. The school, like any other institution, is challenged to reconfigure itself in this context. This research aims to understand why traditional private school requires a change in the contemporaneity. To achieve this purpose, this qualitative study is focused in São Paulo, the most populated city in Brazil, and chose as a case study the transformation discourse of Colégio São Luís, a centenary educational institution with a privileged location in the city. In 2018, after completing 150 years of history and a century located on Avenida Paulista, the institution announced pedagogical changes and the construction of a new school building at another address. To understand the way the school communicates its reasons for undertaking the changes and to explain its characteristics, the methodology of analysis proposed by Discursive Semiotics was used (GREIMAS, 1975) likewise the data coding process proposed by Creswell (2014). The communication toolkit produced by the institution was used as a data source. Besides, interviews were conducted with school managers involved in the remodeling process of educational institutions. The results of this research allowed us to identify the fundamental points related to the characteristics and reasons for the transformation of the school